Role Portrayal of Gay Men in Print Advertisements: A Study on US Market - satyaprakash, shilpa (2010)
This dissertation research is aimed at analyzing the gay roles portrayal in print advertisements by the advertisers. In order to conduct this study, the researcher had selected sample of gay advertisements from the leading US gay magazine and the mainstream magazine. The researcher also developed a coding sheet for the purpose of this analysis. The coding sheet was developed on the basis of various aspects which would enable to find out the various roles that could be portrayed by the gay men in print advertisements. The researcher attempts to study the advertiser’s point of view of looking at the gay men as advertisement objects and tries to analyze their perception for targeting the gay consumers. Detailed analysis would show the frequency of occurrence of a particular type of ad in the magazine and also the consistency that the advertisers maintain for portraying the type of roles of the gay men in US markets.